2002
DOI: 10.1182/blood-2001-12-0252
|View full text |Cite
|
Sign up to set email alerts
|

A subject with a novel type I bare lymphocyte syndrome has tapasin deficiency due to deletion of 4 exons by Alu-mediated recombination

Abstract: HLA class I expression depends on the formation of a peptide-loading complex composed of class I heavy chain; ␤ 2 -microglobulin; the transporter associated with antigen processing (TAP); and tapasin, which links TAP to the heavy chain. Defects in TAP result in a class I deficiency called the type I bare lymphocyte syndrome (BLS). In the present study, we examined a subject with a novel type I BLS who does not exhibit apparent TAP abnormalities but who has a tapasin defect. The subject's TAPASIN gene has a 7.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 23 publications
1
32
0
1
Order By: Relevance
“…Later, Yabe et al (35) described a large homozygous deletion of exons 4 -7 in TAPBP in PBMC obtained from a patient with type II bare lymphocyte syndrome. More recently, Belicha-Villanueva et al (12) revealed a tapasin-loss phenotype by the M553 melanoma cell line, although its underlying mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, Yabe et al (35) described a large homozygous deletion of exons 4 -7 in TAPBP in PBMC obtained from a patient with type II bare lymphocyte syndrome. More recently, Belicha-Villanueva et al (12) revealed a tapasin-loss phenotype by the M553 melanoma cell line, although its underlying mechanism remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Lehmann et al (51) demonstrated that the TAs recognized by the CTLs isolated from recurrent melanoma metastases were different from those recognized by the CTLs isolated from autologous primary lesions. In addition, some of us (14) have shown a shifting of CTL specificity from HLA-A2-MART-1 [27][28][29][30][31][32][33][34][35] complexes to HLA-A2-Tyr 369 -377 complexes in two sequential melanoma metastases with distinct HLA class I abnormalities caused by a mutant ␤ 2 m protein (32). These results are consistent with the possibility that the specificity of a patient's immune response can change in response to changes in the expression of targets by melanoma cells, which have developed immunoescape mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasts with classical observations of murine models (120) which demonstrate that antiviral defense is ensured by class I-restricted CD8 ϩ T cells. Thus, patients with low levels of expression of MHC-I molecules (transporters associated with antigen processing 1 [TAP-1], TAP-2, and tapasin deficiencies) (47,69,73,115,119), as well as those with low numbers of cytotoxic CD8 ϩ ␣␤ T cells (inherited CD8 deficiency) (28), are not particularly susceptible to viral diseases. Equally surprising, patients with either TAP deficiencies or familial CD8 deficiency due to a mutation in the CD8␣ gene (28,32,45,47).…”
Section: Susceptibility To Viral Infectionsmentioning
confidence: 99%
“…It is important to point out that this frequency of the homozygotes is overwhelmingly larger than those of extremely rare variations (reported in less than 30 patients worldwide) known to affect MHC class I-dependent generation of CD8 + T cells in humans (23)(24)(25). Those rare variations include the mutations deficient in the peptide transporter complex TAP and TAP-associated protein TAPASIN, in which patients often suffer from respiratory tract infection and skin granulomatous lesions but sometimes exhibit no clinical problems (23)(24)(25). Based on the results of this study, we would like to propose a careful and long-term analysis of health status in those rs34457782 minor allele populations, particularly in homozygotes, that carry the β5t-G49S variant, in hopes of better understanding the role of the thymoproteasome-dependent positive selection of CD8 + T cells in humans.…”
Section: Cd8mentioning
confidence: 96%
“…The frequency of the 5 homozygotes found in the 9,730 volunteers (0.051%) suggests that the β5t-G49S variation has little or no negative impact on the human populations. It is important to point out that this frequency of the homozygotes is overwhelmingly larger than those of extremely rare variations (reported in less than 30 patients worldwide) known to affect MHC class I-dependent generation of CD8 + T cells in humans (23)(24)(25). Those rare variations include the mutations deficient in the peptide transporter complex TAP and TAP-associated protein TAPASIN, in which patients often suffer from respiratory tract infection and skin granulomatous lesions but sometimes exhibit no clinical problems (23)(24)(25).…”
Section: Cd8mentioning
confidence: 99%